The Supplementary Low Carbon Education E-book for Elementary School Students to Enhance Sustainability Literacy and Global Character Diversity - Anna Permanasari; Indarini Dwi Pursitasari; Toru Matsumoto; Ida Hamidah; Annisa Nurramadhani (Jurnal Pendidikan IPA Indonesia, 2026)
The development of e-books related to low-carbon education (LCE) has been used to enhance sustainability literacy and global character diversity (GCD) among elementary students. The research was conducted to identify the three themes of e-books available to students in phases A, B, and C. The three e-books have developed into a supplementary, ongoing curriculum. The e-books with flip mode and a high validity index have already been implemented and researched using a pre-experimental design in each phase. The e-books were designed as picture stories, equipped with various features to train students’ sustainability literacy and GCD through invitations to think critically, to complete projects, and to express their thinking related to the context and environmental problems. The validity of the e-books was ensured through validation by 5 experts and 20 users, and the data were analyzed using simple statistics and CVI/CVR indexes. The sustainability literacy instrument used was developed and implemented together in the context of learning in Indonesia and Japan (Kitakyushu), with some modifications tailored to each phase. Students' GCD was monitored using a standard questionnaire based on GCD indicators. The research shows that all the e-books have high usability, as indicated by the CVI/CVR scores. The implementation results show, on average, an increase in students’ sustainability literacy from moderate to high. The improvement in students’ GCD was from the moderate to the high category. In addition, the books, attractively packaged with cartoon images, were easy to use with an Android app and very handy, which made the learning experience enjoyable for students.